Fontes de energia e estrutura trófica de peixes em riachos Neotropicais. - Sacramento, Patricia Almeida (2011)
In order to investigate the energy sources that sustain the ichthyofauna food chain of Neotropical streams, the following hypotheses were tested: i) the energy input into the food chain for stream fishes is mainly of allochthonous origin and ii) trophic position determined by dietary (intake) and stable isotope of nitrogen (assimilation) is the same for each fish species analyzed. Fish were collected quarterly between June/2008 and June/2009 through electrofishing. The stomach and portions of muscle for each individual were removed for analysis of diet and isotopic carbon and nitrogen, respectively. The stomach contents were evaluated by frequency and volume for most species, and independent of the stream, the autochthonous resources were the most consumed and were represented mainly by aquatic insects. It was found similar assimilation in fish tissue for allochthonous and autochthonous resources. However, for four species in at least one of the sampling periods (dry and/or rain), algae (phytoplankton and/or periphyton) had a major contribution as sources. The trophic positions for both methods resulted in the third trophic level for most species, except A. altiparanae and P.harpagos (Jurema stream). Thus the first hypothesis was rejected, regardless of the streams, the fishes had their diets based on autochthonous resources, also indicated by the greater assimilation of algae in the muscle tissue of some consumers. The second hypothesis was also rejected, since, although the two methods used in determining the trophic position of fish were in third trophic level, they showed statistically significant differences. It is noteworthy that, although the riparian vegetation did not contribute with significant proportions of carbon, compared to other sources of primary producers, it could have been assimilated by the fish indirectly through macrobentofauna which they were feeding.